Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Novel hybrid of clay, cellulose, and thermoplastics. I. preparation and characterization of composites of ethylene-propylene copolymer - Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Applied Polymer Science, 2007)
{The present study is aimed to prepare hybrid materials by incorporating layered silicates and microcrystalline cellulose into thermoplastic polymer. Using ethylene-propylene (EP) copolymer as thermoplastic polymer matrix and maleated EP (MEP) copolymer as compatibilizer, three types of composites were prepared by (i) melt mixing of cellulose with thermoplastics [
Keywords: abrupt contraction; Arbitrary Lagrangian Eulerian; finite element; simulations

Biocomposites of cellulose reinforced starch: improvement of properties by photo-induced crosslinking - Kumar, Annamalai Pratheep; Singh, Raj Pal (Bioresource Technology, 2008)
In the present study, the composite films have been prepared from the aqueous dispersions of starch with microcrystalline cellulose using glycerol as plasticizer and irradiated under ultraviolet (UV) light using sodium benzoate as photo-sensitizer. Photocrosslinking was characterized by measuring the water absorption under 100% relative humidity, swelling degree and gel fraction in dimethylsulphoxide (DMSC), upon irradiation time. Both, the incorporation of cellulose and photo-irradiation were found to decrease the water absorption, swelling in DMSO and increase the gel fraction. Thermal transitions indicated the anti-plasticization of amylopectin chains at the fiber/matrix interface. With increasing content of cellulose and photo-irradiation time, the tensile modulus and strength were found to improve. It is summarized that the combination of cellulose reinforcement and photo-crosslinking of matrix has improved the physical and mechanical properties. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Biocomposites; cellulose; Photo-irradiation and crosslinking; Starch

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Nanoscale particles for polymer degradation and stabilization-trends and future perspectives - Kumar, Annamalai Pratheep; Depan, Dilip; Tomer, Namrata Singh; Singh, Raj Pal (Progress in Polymer Science, 2009)
The field of nanoscience and nanotechnology is extending the applications of physics, chemistry, biology, engineering and technology into previously unapproached infinitesimal length scales. The polymer-nanoparticles/nanocomposites have been the exponentially growing field of research for developing the materials in last few decades and have been mainly focusing on the structure-property relationships and their development. Since the polymer-nanocomposites have been the staple of modern polymer industry, their durability under various environmental conditions and degradability after their service life are also essential fields of research. Thus, this article is intended to review the status of worldwide research in this aspect. Among various nanoparticulates, clay minerals and carbon nanotubes are more often used in enhancing physical, mechanical and thermal properties of polymers. In very few systems, the nano particulates have been incorporated into polymer as `nano-additives' for both purposes: degradation and stabilization of polymers. The degradation and durability of polymers is reviewed in the presence of nanoparticles/nanocomposites under different environmental conditions. Nanoparticle-induced biodegradation of polymers is also discussed. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanotubes; clay; Degradation and stabilization; Nanocomposites; Nanoparticles; Polymer

Preparation and characterization of bioceramic nanocomposites based on hydroxyapatite (HA) and carboxymethyl cellulose (CMC) - Kumar, Annamalai Pratheep; Mohaideen, Kamal Khaja; Alariqi, Sameh A. S.; Singh, Raj Pal (Macromolecular Research, 2010)
We report the synthesis of biomimetic nanocomposites based on carboxymethyl cellulose (CMC) and hydroxyapatite (HA) nanoparticles via a co-precipitation method. Physico-chemical characterization was performed before and after calcination by Fourier transform infrared (FTIR) spectroscopy, solid state (31)P nuclear magnetic resonance (NMR) spectroscopy, and thermogravimetric analysis (TGA). The formation of nanocomposites was observed by wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDX), and transmission electron microscopy (TEM). The spectral and crystallographic data indicated the formation of hydroxyapatite in the presence of CMC. They were observed as aggregates of HA nanoparticles and CMC, whose sizes were approximately similar to 260 +/- 40 nm. The crystallite size of the hydroxyapatite particles decreased (with 2 wt% 18 +/- 3 nm) with increasing CMC content. The morphological aspects of the calcined samples revealed the sintering ability of HA nanoparticles. Nanocomposites of hydroxyapatite nanoparticles that mimic the process of nucleation and growth in nature can be prepared using biomacromolecules such as CMC.
Keywords: biopolymer; cellulose; hydroxyapatite; Nanoparticles; Particle size; X-ray diffraction